Non-Competition Agreements: Problems of Theory and Practice - D. V. Ahmetyanov (Теоретическая и прикладная юриспруденция)
The realization of freedom of labor by the employee through the termination of employment and the subsequent conclusion of an employment contract with a company that competes with the previous employer is detrimental to the interests of the later. The article contains an attempt to substantiate the necessity and possibility of introducing noncompetition agreements in the Russian labor legislation. In the light of the wide spread of such agreements abroad, the experience of various countries is represented, and the main aspects to be taken into consideration while concluding non-competition agreements are analyzed: 1) the reasonableness of conclusion of such agreements; 2) the form of conclusion; 3) the information about the actions to be performed/not performed by the employee; 4) the categories of employees with whom non-competition agreements may be concluded; 5) the term and the territory of the agreement; 6) compensation of the employee. Author reviewed the current positions of state authorities and the scientific community on the raised issue. In addition, the author provides arguments in favor of using this type of agreements, as well as possible options for adapting it to national legal conditions, taking into account the principle of freedom of labor.